Chiroptical Symmetry Analysis: Exciton Chirality-Based Formulae to Understand the Chiroptical Responses of C(n) and D(n) Symmetric Systems - Castro-Fernández, Silvia (Molecules, 2019)
The high sensitivity of chiroptical responses to conformational changes and supramolecular interactions has prompted an increasing interest in the development of chiroptical applications. However, prediction of and understanding the chiroptical responses of the necessary large systems may not be affordable for calculations at high levels of theory. In order to facilitate the development of chiroptical applications, methodologies capable of evaluating the chiroptical responses of large systems are necessary. The exciton chirality method has been extensively used for the interaction between two independent chromophores through the Davydov model. For systems presenting C(2) or D(2) symmetry, one can get the same results by applying the selection rules. In the present article, the analysis of the selection rules for systems with symmetries C(n) and D(n) with n = 3 and 4 is used to uncover the origin of their chiroptical responses. We foresee that the use of the Chiroptical Symmetry Analysis (CSA) for systems presenting the symmetries explored herein, as well as for systems presenting higher symmetries will serve as a useful tool for the development of chiroptical applications.